Aplikasi Tepung Cangkang Telur dan Pupuk Kandang Ayam Terhadap Pertumbuhan Jagung Manis di Tanah Masam - Najamuddin; Suherman; Putera, Muh. Ikbal (Integrated and Sustainable Agriculture, 2024)
This study aims to increase the productivity of baby corn plants in latosol soil by administering eggshell flour and chicken manure. Latosol soil that dominates Indonesia has high acidity levels and low organic matter content, so it requires effective soil improvers. The experiment used a factorial randomized block plan. Soil analysis showed an increase in pH after treatment. Although statistical analysis did not show a significant difference, the observation results showed that the T3A2 combination gave the best results in plant height and cob length. These results are relevant as initial information for the development of environmentally friendly organic waste-based soil improvers, especially to increase productivity on marginal land. The practical implication is that the use of this organic material can be an economical alternative for farmers to reduce dependence on chemical fertilizers.